2019
DOI: 10.32098/mltj.03.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence of traditional vs fast track recovery methodologies after total arthroplasty for osteoarthritic knee treatment. A retrospective observational study

Abstract: Background: During the last years, programs to enhance postoperative recovery and decrease morbidity after total knee arthroplasty, have been developed across a variety of surgical procedures and referred to as "Fast-Track Surgery". In this study we aimed to find some answers in the management of osteoarthritic patients subjected to total knee arthroplasty, by using the Fast-Track methodology. To this purpose we evaluated parameters such as early mobilization of patients, better pain management, bleeding, poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…A recent study showed that an improvement of five degrees in the range of motion in the knee after surgery along with an improved walking distance could increase the satisfaction rate by 6-8 times [49]. Other studies also agree with the effect of stiffness on satisfaction [50,51]. In the current study the patients' course of recovery was not investigated, only if there were complications or not.…”
Section: Discussionsupporting
confidence: 52%
“…A recent study showed that an improvement of five degrees in the range of motion in the knee after surgery along with an improved walking distance could increase the satisfaction rate by 6-8 times [49]. Other studies also agree with the effect of stiffness on satisfaction [50,51]. In the current study the patients' course of recovery was not investigated, only if there were complications or not.…”
Section: Discussionsupporting
confidence: 52%
“…They had not been sufficiently informed and prepared regarding this preoperatively. However, many studies have shown that "fast track" TKA procedures, with discharge on the day of surgery or the day after, are associated with good satisfaction rates [45][46][47]. We did not differentiate between fast track and conventional surgeries, so we cannot say if our results regarding the percentage of discontentment differ from these other study populations.…”
Section: Discussionmentioning
confidence: 81%
“…They had not been sufficiently informed and prepared regarding this preoperatively. However, many studies have shown that "fast track" TKA procedures, with discharge on the day of surgery or the day after, are associated with good satisfaction rates [52][53][54]. We did not differentiate between fast track and conventional surgeries, so we cannot say if our results regarding the percentage of dissatisfaction differ from these other study populations.…”
Section: Discussionmentioning
confidence: 82%